THE INTERNALIZATION OF PESANTREN EDUCATIONAL VALUES (A Descriptive Study on the Implementation of the Five Core Principles at Al Fattah Islamic Boarding School, Pecalongan, Sukosari, Bondowoso) - Rusydi, Rusydi (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
Pesantren as an educational institution based on religious values ​​that are instilled as an effort to build the character of students through habituation (tatsqief). It aims to print Muslims into insan kamil (perfect humans) and have and master the religious sciences that are lived and practiced sincerely. The Islamic boarding school functions itself as an institution that produces outputs and outcomes as the ideals of the ulama of an Islamic boarding school through educational and teaching activities. Education and teaching are so complex, this is equivalent to the theory which says that